The experiences of adult children with a parent living with a chronic mental illness in Giyani, Limpopo province, South Africa - Hlekani Mabunda; Annie Temane; Marie Poggenpoel (Elsevier, 2023)
Background: Adult children of chronically mentally ill parents are prone to behavioural, emotional, and psychological problems compared to children and teenagers in the general community. Purpose: To gain an understanding of adult children's experiences with a parent living with a chronic mental illness in Giyani, Limpopo Province, South Africa. Design and methods: A qualitative exploratory, descriptive research design was utilised. Ten purposefully sampled adult children with a parent living with a chronic mental illness participated in the study. Data were collected using in-depth phenomenological interviews. Data were analysed utilising Tesch's open-coding method. Results: Adult children experienced having a parent living with a chronic mental illness as a difficult and painful journey filled with confusion. The support and lack of support they received from people around them. They ultimately accepted their situation based on the realisation their parent has a chronic mental illness. Conclusion: Based on the findings, it is recommended that healthcare professionals should promote individuals' mental health and well-being through the provision of mental health education, facilitation of a reduction in mental health stigma in communities, and fostering resilience among adult children with a parent living with a chronic mental illness. The facilitation of support and acceptance of their parent's mental status is also vital for these individuals. Collaboration between families with parental mental illness, the community, social services, mental health services and other relevant organisations and stakeholders were highlighted in supporting these families to achieve better outcomes.